Cloud-Based Iot Monitoring System for Poultry Farming in Nigeria - Gbadamosi, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The monitoring of environmental parameters of poultry farm using IoT applications is no longer a new research area in the field of engineering. However, the cost of implementing most of the reviewed research work seams unaffordable to rural farmers in Nigeria. This could limit the adoption and usage of such devices. In this paper, we present a cost-effective cloud-based IoT monitoring system for poultry farming. The system uses two vital weather parameters- temperature and humidity. The methodology adopted, employed the use of DHT11 sensor (a temperature and humidity sensor) to note every change in temperature and humidity data of the farm environment. The sensed data were extracted, sampled and processed by the microcontroller before transmitting the data to a remote cloud server through the WiFi module. The cloud server (Thingspeak) received the sensed data, analysed the data and plot the data graphically. The plotted graph is viewed from a computer or any smart devices. The result indicates that temperature and humidity values range between 33-38°C and 31-33mmHg respectively. Furthermore, the results show that the device is efficient in monitoring the two environmental parameters. Therefore, the efficiency of the system will no doubt provide much quicker and accurate information about change in temperature and humidity data of farm environment.